Study of depression among patients with type 2 diabetes mellitus at a tertiary care hospital - Imtiyazuddin, M. D.; Soofia, Ameena; Mohammed, Abdul Wasay; Ali, Syed Asim; Dronamraju, Venkata Anil Chandra; Fatima, Arooba (International Journal of Research in Medical Sciences, 2024)
Background: Diabetes and depression are two major issues related to community health. Diabetes patients frequently co-occur with depression. Diabetes patients frequently co-occur with depression, which calls for serious attention because delayed diagnosis and treatment can worsen the patients’ complications. Assessing the prevalence of depression in diabetic patients and identifying the various factors associated with it were the objectives of this research study. Methods: In this study 70 adult patients suffering from type 2 DM participated in this 6-month prospective study. Sociodemographic data and clinical features of the participants were collected. The presence and severity of depressive symptoms in patients have been assessed by a PHQ9 questionnaire. Ethical approval was taken before the commencement of the study. SPSS (Version 20) was used for data analysis. Results: The majority of the patients were from 41-50 years of age group (32.9%) with a female predominance (58.6%), with no symptoms of depression before type 2 DM (92.9%). Most of them had primary education (32.9%) and majority were homemakers (44.3%) residing in urban are (65.7%) living joint family setup (68.6%). Most of them had 11 to 20 years of type 2 DM duration (745.8%) with a high family history of type 2 DM (75.7%). Majority of them were on Oral therapy (47.1%) with ophthalmic complications (32.9%). The majority of them had mild depression (5-9) i.e. 67.1%. Conclusions: Due to patient-specific diabetes management and inappropriate diabetes treatment, the majority of cases were found to have depressive disorders. This article focused on a few common factors and their relationships that lead to depression in people with diabetes.